Lily the thief - Kukkonen, Janne, 1983- (First Second, 2019)
Lily is a novice thief dreaming of making it big and becoming a master, but the Guildmaster of the Thieves only ever gives her pick-pocketing and trespassing jobs. However, while out on one of these simple quests, Lily accidentally uncovers a plot with a strange cult and forgotten gods that could end the world as she knows it.